Molecular characterization of dengue virus reveals regional diversification of serotype 2 in Colombia (2019)
Dengue is hyperendemic in Colombia, where a cyclic behavior of serotype replacement leading to periodic epidemics has been observed for decades. This level of endemicity favors accumulation of dengue virus genetic diversity and could be linked to disease outcome. To assess the genetic diversity of dengue virus type 2 in Colombia, we sequenced the envelope gene of 24 virus isolates from acute cases of dengue or severe dengue fever during the period 2013-2016. The phylogenetic analysis revealed the circulation of the Asian-American genotype of dengue virus type 2 in Colombia during that period, the intra-genotype variability leading to divergence in two recently circulating lineages with differential geographic distribution, as well as the presence of nonsynonymous substitutions accompanying their emergence and diversification. © 2019 The Author(s).